DENGUE: A GLOBAL HEALTH CHALLENGE - CURRENT VIEWS ON PATHOGENESIS, DIAGNOSIS, TREATMENT AND PREVENTION - Aleksandra Drabik,; Elżbieta Bebrysz,; Ida Dunder,; Magdalena Koss,; Mateusz Biszewski,; Karolina Dębek-Kalinowska,; Piotr Bartnik,; Jarosław Baran,; Jan Palmi,; Weronika Ziomek, (International Journal of Innovative Technologies in Social Science, 2025)
Background: Dengue is a global threat expanding its geographic reach and spreading to a growing world population. Up to 3 billion people are at risk. Dengue virus infection can be asymptomatic or sparse, but can also cause dengue hemorrhagic fever and dengue shock syndrome.Aim: The purpose of this article is to highlight the challenges of effective treatment, multi-pronged prevention and safe immunoprophylaxis of dengue virus.Methods: A review of scientific articles published on PubMed and Google Scholar from 2020 to 2025.Results: Due to the number and complexity of dengue serotypes, as well as the antibody-dependent amplification mechanism characteristic of this virus, creating a universal, effective and safe vaccine is a difficult task. It is all the more important because of the lack of specific treatment, which is so necessary in the case of a severe course of the disease in the form of hemorrhagic fever or shock syndrome. It is also necessary to control vectors through chemical, biological and environmental methods.Conclusion: Dengue is now a serious global public health threat that requires urgent action. Key areas for further research and development include a better understanding of pathogenesis, especially in the context of symptomatic DENV infections, and increased work on a variety of treatment and control options, as well as the development of a universal, safe and effective vaccine. The ultimate goal is to reduce the threat of the disease worldwide.